(untitled) (EAAE Joint Publishings, 2026)
Writing is a spatial act - exploring different writing modes may unveil new modes of architectural thinking. When contextualised within the architectural framework, writing takes on a transformative role, capable of opening up possibilities for non-visual relationships and interconnected networks, thereby inviting critical inquiry and discourse. In architectural schools, where the design studio is the central focus, this area usually remains less explored, particularly in undergraduate programmes. However, practising architectural writing brings opportunities to students; for instance, they are introduced to and become familiar with spatial thinking in a literary space where their typically visual preconceptions do not operate. Pursuing this perspective, this paper explores how effectively using writing as a design tool can uncover new and unconventional perspectives on architecture and proposes architectural writing as an interdisciplinary learning tool for guiding future architects and architectural design researchers. These issues are examined through an in-depth study of pedagogical objectives and outcomes of the Architectural Speaking and Writing course, a mandatory subject for third-year undergraduate students. The course is structured as a writing laboratory that closely examines forms of architectural writing as primary instruments for finding a critical voice, engaging in critical dialogue, and communicating with the wider public. Through introducing the design of the course structure and analysing the writing exercises, this paper addresses the crucial role that diverse mediums and methods of expression play for students to connect their internal narratives with external realities in architectural education while altering the dominant position of the educator towards a facilitator.